Micro growth of freshwater bivalve (Paxyodon syrmatophorus) with marking fluorochrome calcein - Barros, Mara Rúbia Ferreira; Martins, Lucas Garcia; Abreu, Valdo Sena; dos Santos, Wagner Cesar Rosa; das Chagas, Rafael Anaisce; Herrmann, Marko (Universidade Federal Rural da Amazônia, Brazil, 2020)
Micro growth of freshwater bivalve (Paxyodon syrmatophorus) with marking fluorochrome calcein to validate the assumption of ring formation grown in the Maratauira river, Abaetetuba, Pará
Keywords: Abaetetuba; Calcein; growth; Para; Paxyodon syrmatophorus